Menelisik Kebijakan Moderasi Beragama Dalam Pandangan Kebebasan Beragama Atau Berkeyakinan - Manuel, Elkristi Ferdinan (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
This study critically examines religious moderation in Indonesia by examining how the policy operates within the context of freedom of religion or belief (KBB), particularly for minority groups. Top-down moderation creates "forced tolerance," as the state determines the standards of moderate religiosity based on the majority’s interpretation. This has the potential to reduce pluralism, suppress minority religious expression, and give rise to state-legalized symbolic violence. The findings reveal a contradiction between the goal of harmony and the practice of restricting rights. With a critical legal approach, this study offers a framework for reformulation of religious moderation that is more in line with pluralism and human rights principles.